2018
DOI: 10.31235/osf.io/hy9wt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“There’s Always Winners and Losers”: Traditional Masculinity, Resource Dependence, and Post-Disaster Environmental Complacency

Abstract: The 2013 Southern Alberta flood was a costly and devastating event. The literature suggests that such disasters have the potential to spur greater environmentalism and environmental action, as residents make connections between global environmental change and local events. However, the literature also suggests that residents in communities dependent on fossil fuel extraction might see technological disasters, like oil spills, as threats to their economic well-being, thereby limiting environmental reflexivity. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…This finding is consistent with the work of Milnes and Haney (2017), who found that flood‐affected residents in Calgary expressed an increase in post‐disaster environmental concern, but this newfound concern was largely gendered. Disaster‐affected women were more than twice as likely to say that their environmental views changed as a result of experiencing the flood; disaster‐affected men, however, expressed more denial, reluctance, and complacency and viewed the disaster as a focusing event which drew undesired attention to climate change (Bishop 2014).…”
Section: Literature Reviewsupporting
confidence: 91%
“…This finding is consistent with the work of Milnes and Haney (2017), who found that flood‐affected residents in Calgary expressed an increase in post‐disaster environmental concern, but this newfound concern was largely gendered. Disaster‐affected women were more than twice as likely to say that their environmental views changed as a result of experiencing the flood; disaster‐affected men, however, expressed more denial, reluctance, and complacency and viewed the disaster as a focusing event which drew undesired attention to climate change (Bishop 2014).…”
Section: Literature Reviewsupporting
confidence: 91%
“…For a more in‐depth description of data and methods, see also Haney (, ) and Milnes and Haney (). Table includes the descriptive statistics and metrics for all the variables used in the models.…”
Section: Methodsmentioning
confidence: 99%
“…The literature reveals that several demographic factors are robust predictors of risk perception, including income (Babcicky & Seebauer, ; Cutler, ), gender (Enarson & Scanlon, ; Henwood, Pidgeon, & Parkhill, ; Milnes & Haney, ; Morioka, ), race and ethnicity (Spence, Lachlan, & Griffin, ), occupation (Kouabenan, ), age (Kellens, Zaalberg, Neutens, Vanneuville, & De Maeyer, ; Tuohy & Stephens, ), ability/disability (Alexander, Gaillard, & Wisner, ), educational attainment, and access to information (Park & Vedlitz, ). It is of note that age is a significant factor regarding how people wish to receive warnings and risk‐related information, with younger people preferring newer forms of media (i.e., social media) and older people preferring traditional forms of media (i.e., television) (Feldman et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extractive activity leaves physical legacy such as infrastructure or pollution in the built environment which must be managed and/or remediated (Martinez-Fernandez and Wu, 2009). However, resource extraction may also leave cultural, political and psychological legacy such as unwillingness among municipal governments to accept the need to manage decline (Schatz, 2017); reluctance to reflect on environmental implications of extraction due to local economic dependency (Milnes and Haney, 2017); continued and unwarranted focus on developing largescale infrastructure (He et al, 2017); the need for governors to pick up the aftermath of actions and developments undertaken by private-sector operators (Martinez-Fernandez et al, 2012); and inequality and deprivation exacerbated by uneven distribution of high incomes from extraction-related employment (Reeson et al, 2012).…”
Section: Shrinking Cities and Managed Transitionsmentioning
confidence: 99%